2014
DOI: 10.1007/s40003-014-0128-4
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Distribution of Iron from Different Iron Sources Applied as Foliar Sprays to Chlorotic Leaves of Low-Chill Peach Cultivars

Abstract: A greenhouse experiment was carried out to examine the uptake and distribution pattern of iron applied through different iron sources to chlorotic leaves of three low-chill peach cultivars viz. Saharanpur Prabhat, Shan-e-Punjab, and Pratap. The plants were grown in sandy loam soil containing 30 g CaCO 3 kg -1 soil in plastic pots. Upon the onset of iron deficiency symptoms, separate foliar spray treatments were given using Fe-sulfate [0.5 % (w/v) and 1.0 % (w/v)], Fe-citrate [0.5 % (w/v) and 1.0 % (w/v)], and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Rios et al (2016) used the Perls blue method to trace Fe uptake pathway in leaves of Prunus rootstock and found that inorganic Fe salts caused larger leaf Fe concentration increases than Fe-EDTA. Under conditions of Fe deficiency, the highest Fe uptake and distribution thereof in leaves were recorded after foliar spray treatment with FeSO 4 followed by Fe-citrate and Fe-EDTA (Chakraborty et al 2014a). Similarly, all Fe sources significantly increased the leaf chlorophyll of peach, as well as both the "physiologically active" and total Fe concentrations of the leaves compared with controls; the highest values were noted with foliar-applied 1% FeSO 4 (Chakraborty et al 2014b).…”
Section: Disadvantages Of Chelating Fertilizermentioning
confidence: 85%
“…Rios et al (2016) used the Perls blue method to trace Fe uptake pathway in leaves of Prunus rootstock and found that inorganic Fe salts caused larger leaf Fe concentration increases than Fe-EDTA. Under conditions of Fe deficiency, the highest Fe uptake and distribution thereof in leaves were recorded after foliar spray treatment with FeSO 4 followed by Fe-citrate and Fe-EDTA (Chakraborty et al 2014a). Similarly, all Fe sources significantly increased the leaf chlorophyll of peach, as well as both the "physiologically active" and total Fe concentrations of the leaves compared with controls; the highest values were noted with foliar-applied 1% FeSO 4 (Chakraborty et al 2014b).…”
Section: Disadvantages Of Chelating Fertilizermentioning
confidence: 85%
“…Yüksek pH ve bikarbonat konsantrasyonlarından kaynaklı kalkerli topraklarda yetişen bitkileri etkileyen demir eksikliği klorozu (IDC), bitkilerin ortak bir beslenme bozukluğudur [4]. Özellikle sulamayla değerlendirilen kurak ve yarı kurak bölgelerde kalkerli topraklarda demir klorozu yaygın bir problemdir.…”
Section: Introductionunclassified